A question of TiME: how microenvironmental interactions shape response to immunotherapy in CLL and Richter Transformation - vom Stein, Alexander F.; Nguyen, Phuong-Hien; ten Hacken, Elisa (Frontiers in Immunology, 2025)
Immunotherapy has revolutionized the treatment landscape for many cancers, including some B- cell lymphomas. Immune checkpoint blockade, CAR-T cells and bispecific antibodies have shown promise for the treatment of Richter Transformation (RT) but have displayed reduced activity in chronic lymphocytic leukemia (CLL). These observations suggest that, besides the intrinsic differences between CLL cells and transformed RT cells, there are also marked differences in tumor immune microenvironmental (TiME) composition and tumor-immune cell interactions between these two entities, which remain to be fully characterized. In this perspective, we highlight recent studies describing the TiME in CLL and RT, utilizing both patient-derived tissues and novel mouse models. We then provide a brief overview of current clinical trials employing immunotherapy in CLL and RT and offer a perspective on current challenges and future research efforts in the field.